USING GIS-BASED PROJECTS IN LEARNING: STUDENTS HELP DISABLED PEDESTRIANS IN THEIR SCHOOL DISTRICT - Ali DEMIRCI; Ahmet KARABURUN; Mehmet ÜNLÜ; Ramazan ÖZEY (European Journal of Geography)
This study outlines a GIS-based project conducte d in a public high school in Istanbul, Turkey with the support of the Scientific and Technological Research Council of Turkey (TÜBİTAK) in 2010. Fifteen 9th and 10th grade students worked as a group to determine how livable their district was for disabled pedestrians. The project lasted for one and a half years and students investigated the 251 kilometers of sidewalks in the district of Sisli. The students mapped all the objects that occupied the sidewalks, measur ed the widths and heights of the sidewalks at more than three thousand points, and located all the ramps cons tructed at each end of the sidewalks for those who use wheelchairs. At the end of the project, th e students produced a map showing where disabled pedestrians can travel on sidewalks by themselves in the district. The project revealed that GIS is an important learning and teaching t ool for schools and an important platform to bring school and other institutions together to solve social problems.